ACADEMICIAN V.V. BARTOLD AND CAUCASIAN STUDIES - Buharin, Mihail Dmitrievic (History, Archeology and Ethnography of the Caucasus, 2025)
The study of the Caucasus did not constitute Academician V.V. Bartold’s primary academic focus. Nevertheless, as a scholar specializing in medieval history and literature (Turkologist, Iranist, and Arabist), an Islamic scholar, and an administrator, Bartold frequently engaged with the history of the Caucasus. His sustained interest in this region is evidenced by his correspondence with Academician N.Ya. Marr, an archaeologist, literary scholar, and linguist, with over fifty documents discovered and published. The V.V. Bartold collection, housed at the St. Petersburg Branch of the Archives of the Russian Academy of Sciences (SPbB ARAS), includes both the original offprints of Bartold’s published works on various aspects of Caucasian history and autographs of unpublished works. These materials indicate that the Caucasus held a more significant place in Bartold’s scholarly activity than previously acknowledged, with several of these works remaining relevant to contemporary scholarship. During 1922–1923, Russian academic and cultural institutions faced a challenging campaign to transfer historical and cultural artifacts of Georgian or presumed Georgian origin to Georgia. In this context, V.V. Bartold, serving as deputy chairman of the State Academy of the History of Material Culture (GAIMK) and as a colleague of S.F. Oldenburg at GAIMK and the Russian Academy of Sciences, actively participated in efforts to oppose this campaign. Bartold contributed to the scholarly and museum communities’ endeavors to halt the transfer process or, at minimum, to reduce the number of artifacts transferred. A report authored by Bartold, preserved in the V.V. Bartold collection at the SPbB ARAS, documents a meeting of the GAIMK Council. In this report, Bartold articulates, on behalf of GAIMK, the scholarly position advocating for the preservation of national historical and cultural heritage, the maintenance of globally significant scientific and cultural centers, and the integrity of museum and library collections.